Out of Control: The Rhetoric of Gastrointestinal Disorders - Amy Vidali (Disability Studies Quarterly, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This article suggests that IBS, and its relationship to disability studies, can be better understood by examining the rhetorics surrounding gastrointestinal (GI) disorders. To understand the function of GI rhetorics, I examine three rhetorical sites: (1) communal meal settings and the rhetorical politics of food refusal; (2) historical and contemporary texts that gender gastrointestinal distress; and (3) rhetorics of cure and control in advertising for GI-related products, particularly Zelnorm and Activia. The article concludes that changing attitudes about gastrointestinal disorders is not so much about controlling our bodies, but reclaiming the rhetorics of these disorders.